POSTERIOR VERSUS ANTERIOR APPROACH TO TOTAL HIP ARTHROPLASTY: A SYSTEMATIC REVIEW AND META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS - LORENZO FAGOTTI; GUILHERME GUADAGNINI FALOTICO; DANIEL AUGUSTO MARANHO; OLUFEMI R. AYENI; BENNO EJNISMAN; MOISES COHEN; DIEGO COSTA ASTUR (Acta Ortopédica Brasileira, 2021)
ABSTRACT Objective: To perform a systematic review and meta-analysis to compare clinical and surgical outcomes of posterior versus anterior approach to primary total hip arthroplasty (THA). Methods: This study followed the standard methodology established by the Cochrane Handbook and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Two independent reviewers searched for randomized controlled trials comparing posterior an anterior approach to primary THA with at least one quantifiable functional outcome published in the PubMed, Cochrane, and Virtual Health Library databases. Results: The analysis included ten randomized controlled trials conducted with 774 patients. The posterior approach was associated with shorter operative time (mean of 15.98 minutes shorter, 95% CI 11.21 to 20.76, p < 0.00001) while the anterior approach was associated with shorter length of hospital stay (0.31 days or about eight hours shorter, 95% CI 0.12 to 0.51, p = 0.002) and greater earlier improvement in functional outcomes up to six months from the procedure (mean Harris Hip Score of 4.06 points greater, 95% CI 2.23 to 5.88, p < 0.0001). Conclusion: Whereas the posterior approach to primary THA is associated with a shorter operative time, the anterior approach has the potential to decrease the length of stay and provide greater short-term functional restoration. Level of evidence I, Systematic Review and Meta-Analysis.